2015
DOI: 10.1016/j.cub.2014.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Increased Affluence Explains the Emergence of Ascetic Wisdoms and Moralizing Religions

Abstract: We discussed several possible causal pathways, including the development of literacy and urban life, and put forward the idea, inspired by life history theory, that absolute affluence would have impacted human motivation and reward systems, nudging people away from short-term strategies (resource acquisition and coercive interactions) and promoting long-term strategies (self-control techniques and cooperative interactions).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 20 publications
4
101
0
2
Order By: Relevance
“…inferring emotions in other people (social inference, theory of mind) (Spunt and Lieberman, 2012; Skerry and Saxe, 2015]…”
Section: How To Get Confused About Emotionsmentioning
confidence: 99%
See 2 more Smart Citations
“…inferring emotions in other people (social inference, theory of mind) (Spunt and Lieberman, 2012; Skerry and Saxe, 2015]…”
Section: How To Get Confused About Emotionsmentioning
confidence: 99%
“…On the other hand, semantic knowledge for emotions has indeed been mapped, at least across cortex, and can be compared with semantic knowledge of many other concepts for which we have words (Huth et al , 2016). Another study (Skerry and Saxe, 2015) was notable for comparing similarity amongst neural representations with conceptual similarity in how people rate emotions according to several popular psychological theories (arousal/valence; basic emotions; appraisal dimensions). That study (Skerry and Saxe, 2015) found that attributions about other people’s emotions that we make from thinking about the situations in which people find themselves activate representations in a system of brain structures known to be involved in mental state attribution more generally (such as the temporoparietal junction, dorsomedial prefrontal cortex and precuneus); the best match between neural and psychological similarity structures held for ratings on appraisal dimensions.…”
Section: A Framework For Neuroimaging Studies Of Emotion States: Systmentioning
confidence: 99%
See 1 more Smart Citation
“…A full discussion of this debate is beyond the scope of this article, but we consider the by-product view, most notably advanced by Boyer (2001), more likely. See for example Baumard, Hyafil, Morris, and Boyer (2015) for a cogent critique of Norenzayan (2013). conceptual repertoire? We address this question by focusing on the case study of the God concept in Christian theology.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Morris has charted the growth of energy capture in the five most intensive agricultural zones from 11000 BC to 1 CE (Baumard, Hyafil, Morris & Boyer 2015). In this study, variables such as house size, population density, and population of the main city are used as proxies for energy capture.…”
Section: Introduction: Is Long‐term Human Evolutionary Change In Somementioning
confidence: 99%